The effectiveness of augmented reality in enhancing learning outcomes in a microcontroller course - Mukhlisin, Mukhlisin; Asrifan, Andi; Cardoso, Luís Miguel Oliveira de Barros (Jurnal Inovasi Teknologi Pendidikan, 2025)
One significant challenge in technical and vocational education is students’ difficulty in achieving a deep conceptual understanding, particularly in complex subjects such as microcontrollers. Traditional methods often lack interactivity and real-world context, leading to low engagement and learning outcomes. Augmented Reality (AR) provides an immersive and interactive learning experience that enables students to visualize abstract concepts. This study examined the impact of AR-based instructional media on learning outcomes in a Microcontroller course, using a true experimental design (Solomon Four Group Design). Four student groups from four vocational higher education institutions in Makassar participated (total N = 143). Two groups received AR-based instruction, and two received conventional teaching; two of the groups also completed a pretest. Learning outcomes were assessed through essay-format pretests and posttests aligned with microcontroller learning indicators. Learning improvement was measured using normalized gain scores, and data were analyzed with normality tests, homogeneity tests, ANCOVA, independent t-tests, and N-Gain analysis. Results showed that AR significantly improved learning outcomes, with experimental groups achieving a mean gain score of 0.75 (in the high category), compared to 0.16 (in the low category) in control groups. Statistical tests confirmed significant differences between groups (p < 0.05), while comparisons among control groups indicated no substantial pretest effect. This confirms that the learning improvement resulted from the AR intervention. The findings suggest AR-based instructional media effectively enhance conceptual understanding, learning quality, and student engagement in technical education. The study concludes that AR is a viable instructional tool in vocational learning and recommends its broader use and further development in similar educational contexts.